Village Government Roles in Strengthening Women’s Empowerment Programs: Peran Pemerintah Desa dalam Menguatkan Program Pemberdayaan Perempuan - Harianti, Iis; Choiriyah, Ilmi Usrotin (Indonesian Journal of Public Policy Review, 2025)
General Background: Women’s empowerment plays a crucial role in realizing inclusive and sustainable village development. Specific Background: Despite the growing attention to gender equality, women in rural areas often face limited access to resources, participation, and decision-making processes. Knowledge Gap: Previous studies have not fully analyzed how village governments operationalize their roles institutionally to support women’s empowerment through integrated community-based strategies. Aims: This study aims to analyze the roles of the Jambangan Village Government in supporting women’s empowerment based on Talcott Parsons’ four-role framework: motivator, facilitator, mobilizer, and regulator. Results: The findings show that the village government has effectively implemented diverse empowerment initiatives such as skills training, women’s cooperatives, and health cadre strengthening, though constraints remain in participation levels, resources, and legal regulations. Novelty: This research offers a comprehensive analysis combining sociological theory and administrative functions to explain how grassroots governance contributes to sustainable gender empowerment. Implications: Strengthening legal frameworks and inclusive mobilization strategies are essential to sustain empowerment initiatives and promote gender-responsive local governance. Highlights: Village governance shapes women’s empowerment through four functional roles. Legal and institutional support remains limited yet critical. Integrating social participation strengthens sustainable village development. Keywords: Women’s Empowerment, Village Government, Public Policy, Gender Equality, Local Governance